Cytomegalovirus Infection in Pediatric Severe Ulcerative Colitis—A Multicenter Study from the Pediatric Inflammatory Bowel Disease Porto Group of the European Society of Pediatric Gastroenterology, Hepatology and Nutrition. Issue 3 (March 2018) - Cohen, Shlomi; Martinez-Vinson, Christine; Aloi, Marina; Turner, Dan; Assa, Amit; de Ridder, Lissy; Wolters, Victorien M.; de Meij, Tim; Alvisi, Patrizia; Bronsky, Jiri; Kopylov, Uri
Abstract : Background: Data on the clinical course and outcomes of pediatric patients with cytomegalovirus (CMV) infection complicating acute severe ulcerative colitis (ASC) are very limited. The aim of our study was to compare outcomes of children with ASC who were CMV positive or CMV negative. Methods: This was a multicenter retrospective case-controlled study, from centers affiliated with the Pediatric Inflammatory Bowel Disease Porto Group of European Society of Pediatric Gastroenterology, Hepatology, and Nutrition. We included CMV-positive children hospitalized for ASC and compared their colectomy rate during hospitalization and up to 1 year thereafter, matched with CMV-negative controls. Results: A total of 56 children were included; 15 CMV positive and 41 CMV negative. More CMV-positive patients were resistant to intravenous corticosteroids as compared with CMV negative (93% and 56% respectively, P = 0.009). Fourteen of the CMV-positive children (93%) were treated with ganciclovir [5/14 (36%) with 5 mg/kg and 9/14 (64%) with 10 mg/kg]. During hospitalization, 3 (20%) CMV-positive and 3 (7.8%) CMV-negative patients required colectomy ( P = 0.17). By 12 months, 5 (33%) and 5 (13%) CMV-positive and CMV-negative patients required colectomy, respectively ( P = 0.049); the significance was not retained on multivariate analysis. Conclusions: A higher prevalence of CMVpositivity was found in pediatric ulcerative colitis patients who required colectomy within 12 months of hospitalization for ASC. Further studies are needed to clarify the impact of CMV infection on the outcome of acute severe colitis in pediatric patients.